PERANCANGAN PROTOTYPE JEMURAN PAKAIAN OTOMATIS MENGGUNAKAN SENSOR LDR DAN SENSOR BASAH BERBASIS ARDUINO - Setyaji, Alvia Setyaji; Handoko, Koko (Computer Science and Industrial Engineering, 2019)
At the time of the rainy season, some people especially housewives will worried when doing homework like hanging clothes. Added to this is the result of global warming that is occurring at this time causing a very difficult change of weather. There is a sudden change of weather from hot to rain or vice versa, consequently it could be clothes that are not dry when rain and forget to lifted. From the description of the problem above, the author get the idea to create a towing tool that can work clothes automatically. The tool uses the Arduino Uno microcontroller coupled with wet sensor (water) and light sensor (LDR).